Perceptions, patterns, and arms: an analysis of the panorama of brazilian violence - Steeves, Geoffrey Michael (2014)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Sócio Econômico, Programa de Pós-Graduação em Economia, Florianópolis, 2014